Kenya's first Biennial Transparency Report (BTR): First BTR to The United Nations Framework Convention on Climate Change (UNFCCC) - Government of Kenya (2024)
Kenya's first Biennial Transparency Report (BTR1) captures the country's progress in implementing its first updated Nationally Determined Contribution (NDC). The report captures climate actions of state and non-state actors, demonstrating concerted efforts to reduce greenhouse gas emissions and respond to the impacts of climate change across sectors.